ANALISIS PENGUKURAN KINERJA KEUANGAN PERBANKAN MENGGUNAKAN METODE CAMEL DAN MODEL ALTMAN - Manfaluthy, Lutfi Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to observe the measurement of banking financial analysis performance by using CAMEL method and Altman model at the banking companies which are listed in Indonesia Stock Exchange (IDX) in period of 2007-2012.The research samples consist of 28 banking companies which are listed in Indonesia Stock Exchange (IDX) with the total observation are 168 and it was selected by using purposive sampling. The data of audit financial report obtained from Indo-Exchange File (IDX). This research is using non-parametric statistic test to test the comparison between CAMEL method and Altman model in measuring the banking health. Crosstab is used to measure the CAMEL method and Altman model.The research result with non-parametric statistic test by using McNemar test shows that CAMEL method and Altman model give a different result in measuring the health of banking financial. Therefore, the CAMEL method has a tendency to give health predicate, while in the Altman model it has tendency to give bankruptcy or unhealthy predicate.Keywords: CAMEL Method, Altman Model, The Health of Banking Financial Report.